Art history contemporary perspectives on method - Arnold, Dana. (Malden, Mass. Wiley-Blackwell, 2010)
Examines the various patterns and approaches to the discipline of art history exhibited across the scholarship of all periods over the last 30 years, resulting in a cross section of art history in all its complexities and a timely survey of its historiography. This collection of newly commissioned essays by a leading group of international scholars examines the various patterns and approaches to the discipline of art history over the last 30 years. The book takes a trans-disciplinary approach to the history of Art History, presenting a cross section of the field in all its complexities.
1. Art history : contemporary perspectives on method / Dana Arnold -- 2. Sexing the canvas : calling on the medium / Nicholas Chare -- 3. Phenomenology and interpretation beyond the sesh / Amanda Boetzkes -- 4. Surveying contemporary art : post-war, postmodern, and then what? / Dan Karlholm -- 5. Michel Foucault and the point of painting / Catherine M. Soussloff -- 6. Karl Mannheim and Alois Riegl : from art history to the sociology of culture -- 7. Art fiction / H. Perry Chapman -- 8. Dancing years, or writing as a way out / Adrian Rifkin -- Index.
"Originally published as Volume 32, Issue 4 of Art History."
Keywords: Art -- Historiography